The Impact Of Human Resource Information Systems And Artificial Intelligence On Defense Industry Performance - Riatmaja, Dodi Setiawan; Sukmaningrum, Dinda; Nurcahyo, Narwanto; Saptyawati, Laksmindra (Nomico, 2024)
The purpose of this research is to investigate how HRIS and AI have influenced the productivity of the military sector in this era of disruption. This inquiry will use a quantitative approach to its methods. The sample pool consisted of one hundred fifty persons who were employed in the military industry. As the main form of data collecting, we will be sending out questionnaires to all of the participants. A Likert scale is provided in the questionnaire, and it is used to assign ratings to the various pieces of information. In order to do an analysis on the data, structured equation modeling in SmartPLS 3.0 was used. In this research, the variable known as "employee performance" acts as the dependent variable, while the variables known as "HRIS" and "work satisfaction" serve as the independent variables. The significance level that was discovered in the data analysis for this research provides evidence in support of the hypothesis that HRIS has a beneficial effect on productivity in the workplace. The HRIS program will be more precise, exact, and comprehensive to the extent that the employee's performance on work assignments is higher. Improving the defense industry's ability to make intelligent decisions about its human resource allocations by implementing methodical HRIS procedures, such as the collection, storage, maintenance, retrieval, and validation of data. Plans for the strategic use of information technology may have an impact on the future direction of the military industry by modifying both the extent to which human resources are used and the depth to which individuals comprehend the context in which they operate. There is a correlation between the use of artificial intelligence (AI) in the workplace and increased levels of productivity